THE STRENGTHS AND WEAKNESSES OF USING GOOGLE CLASSROOM FOR BLENDED LEARNING - Sumartini, Ni Luh Putu; Eka Agustina, Dewa Ayu; Adnyani, Luh Diah Surya (Universitas Pendidikan Ganesha, 2021)
Learning Technology plays a crucial role in the development of education in Indonesia. Teachers should use IT to increase students' learning motivation. Blended learning is one way teachers should facilitate learning interactions that combine conventional learning methods with technology. Google Classroom is one of the most accessible applications to help teachers and students need more time to study online learning. In online learning, several applications can have both positive and negative impacts during the process. This study aims to analyze. Advantages and Disadvantages of Google Classroom for Mixed Learning. This type of research is qualitative. The subjects of this study were 12 students. Data collection was done by observation and interviews. The instrument used to collect data is a questionnaire. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The result of the research is that 85% of students have difficulty communicating in writing in the comments column. In addition, 5% of students stated that it is easy to share and share ideas during online interactions. In contrast, 40% of students stated that Google Classroom was easy to operate and use.